OXIDATION RESISTANCE BEHAVIOR OF ALUMINA-FORMING AUSTENITIC STAINLESS-STEEL FE-20NI-14CR-6AL-1.2TI-1NB-0.2C-0.1Y WITH ADDITION VARIATION OF SILICON AT 900Â°C - INTAN FATMAWATI, LULU
The demand for electricity in Indonesia is predicted to increase every year as the utilization of electricity in various applications increases massively. Based on RUPTL PT. PLN 2021-2030, electricity demand growth in 2030 will reach 390 TWh. The production of more clean energy is one of the things that is currently being considered. Increasing the efficiency of heat conversion power plants can be done by increasing the operating temperature. Alumina-forming austenitic stainless steel (AFA SS) alloy is one of the candidate materials for those applications. In this study, AFA SS oxidation behavior with the addition variation of silicon was investigated by the isothermal semi-cyclic oxidation method.